Biochemical Parameters in Broiler Chickens Vaccinated Against ND, IB and IBD - Talebi, A. (International Journal of Poultry Science, 2006)
Poultry diseases affect serum values of some biochemical parameters in chickens and a high degree of correlation between serum concentration of these parameters and humoral immunity against some poultry diseases has been reported. During this investigation, effects of vaccination against Newcastle disease, infectious bronchitis and infectious bursal disease on some selected biochemical parameters including albumin, calcium, chloride, cholesterol, glucose, magnesium, phosphorus, protein and triglycerides were studied. The results indicate that differences in values of the biochemical parameters within chickens of various ages were significant (P< 0.05), while between chickens of each group at specific age were not significant. Comparison values of the biochemical parameters between groups revealed that only values of triglyceride, total protein and albumin of vaccinated chickens were significantly (P< 0.05) differed from those values of corresponding biochemical parameters of control chickens. In conclusion, serum concentrations of biochemical parameters are age-dependent and some of them differ by vaccination.